(untitled) (Swiss Medical Weekly, 2019)
BACKGROUND Infants born very preterm are at higher risk of long-term neurodevelopmental problems than children born at term. Although there are increasing numbers of reports on outcomes from international cohorts of premature infants, a Swiss national report on infants after 2 years of age is lacking. AIMS OF THE STUDY To describe neurodevelopmental outcomes at early school age of preterm children born in Switzerland with a special focus on the cognitive abilities. METHODS This prospective national cohort study included children born alive before 30 weeks of gestation in 2006. At 5 years of age, children underwent a neurological examination and intelligence testing with the Kaufman Assessment Battery for Children first edition (K-ABC). We assessed the mental processing composite score (MPC) and its subscales to explore specific cognitive deficits. The primary outcome was cognitive impairment (MPC score <−1 standard deviation from the normative mean), motor impairment (cerebral palsy), or sensory impairment (any visual or hearing deficiency). The need for early intervention or therapies and the association of perinatal factors with cognitive impairment were secondary and tertiary outcomes. Logistic regression models were used to analyse associations between neonatal factors and cognitive outcome. RESULTS Of 289 survivors, 235 were assessed. Of the 199 children with results obtained from the K-ABC, 42 (21%) showed cognitive impairment and 80 (40%) showed impairment in short-term memory. Cerebral palsy was diagnosed in 14 (6%), and visual and auditory impairment in 36 (15%) and 12 (5%) children, respectively; 63 (27%) needed early intervention or therapies. Cognitive impairment was associated with low socioeconomic status, but not with gestational age, small birthweight for gestational age, bronchodysplasia, or significant brain injury. A total of 146 children (63%) survived without any impairment. CONCLUSION This is the first study to report neurodevelopmental outcomes at early school age in a Swiss cohort. The majority had favourable outcomes, but 21% of children demonstrated cognitive impairment, which was most pronounced in short-term memory. Our findings were similar to those of international cohorts and indicate that preterm children born before 300/7 gestational weeks, especially those living in unfavourable social environments, are at an increased risk of cognitive impairment and need close monitoring beyond early school age. Trial registration no KEK-ZH-Nr.2014-0552